Effect of oral antibiotics after two-stage revision for periprosthetic joint infection on subsequent antibiotic resistance within a national cohort of United States veterans - J. Payne; J. Payne; J. D. Sutton; B. E. Blackburn; S. Bansod; S. Bansod; H. Imlay; H. Imlay; E. S. Spivak; E. S. Spivak; J. Pupaibool; J. Pupaibool; et al. (Journal of Bone and Joint Infection)
Background: Prior studies have indicated that administration of prolonged courses of oral antibiotics after Stage 2 reimplantation surgery for periprosthetic joint infection (PJI) results in a lower rate of recurrent PJI. However, there is concern that this antibiotic usage results in an increased risk of antibiotic resistance in any subsequent PJI that does occur.